Trend of smoking and tobacco use in Sri Lanka 1960 - 2010: is it affected by cigarette pricing? - Athauda, L.K.; Wickremasinghe, A.R. (Sri lanka Medical Association, 2015)
Introduction and objectives: The prevalence of smoking among adults in Sri Lanka in 2012 was estimated as 9.3%, with prevalences being 18.6% for males and 0.2% for females. This study aimed to describe smoking and tobacco use trends from 1960-2010 and the influence of pricing on trends. METHOD: Tobacco consumption data was obtained from the Food and Agricultural Organization database, cigarette consumption from the World Bank database, population data from the UN database and cigarette pricing and current prevalence of smoking from the Alcohol and Drug Information Centre. Correlation and regression analysis were carried out. Results: The average cigarettes sticks smoked from 1960-2004, were 289+ 58.66 sticks/capita/year and average tobacco use from 1960-2010 was 560.87+223.43 kg/capita/year. Between1960-1977, the number of cigarettes smoked increased on average at a rate of 11.5 per capita/year; and since 1978 smoking decreased by 2.33sticks/capita/year. If only males are considered as smokers In Sri Lanka, the number of cigarettes smoked per male per year increased on average by 22.9 between 1960 and 1977; the average decrease after 1978 among males was 4.17 cigarettes per male per year. Between 2000 and 2012, the smoking prevalence is negatively correlated with the increase in cigarette pricing (r=0.469, p=0.034: R2=0.408). There was a decrease in mortality due to respiratory neoplasms beginning in 1995; this decrease corresponds to the decrease in smoking since 1978, having a lag period of about 15 years (r= 0.002 p=0.021, R2=0.151). CONCLUSION: Smoking and total tobacco consumption has been decreasing since 1978, similar to the trend observed globally. Tobacco pricing negatively influences smoking.
Poster Presentation Abstract (PP112), 128th Annual Scientific Sessions, Sri Lanka Medical Association, 6th-8th July 2015 Colombo, Sri Lanka
Keywords: smoking